2020
DOI: 10.1111/pce.13710
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Cytosolic glyceraldehyde‐3‐phosphate dehydrogenase 2/5/6 increase drought tolerance via stomatal movement and reactive oxygen species scavenging in wheat

Abstract: Drought is a major threat to wheat growth and crop productivity. However, there has been only limited success in developing drought‐hardy cultivars. This lack of progress is due, at least in part, to a lack of understanding of the molecular mechanisms of drought tolerance in wheat. Here, we evaluated the potential role of three cytosolic glyceraldehyde‐3‐phosphate dehydrogenases (TaGAPC2/5/6) under drought stress in wheat and Arabidopsis. We found that TaGAPC2/5/6 all positively responded to drought stress via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 84 publications
0
4
0
1
Order By: Relevance
“…Consistently, we found that WRKY33 exhibited a similar expression pattern to ATL31 and the expression levels of both genes were enhanced by Cd stress (Figures 1c,d, and 5g,h). Several studies have shown that WRKY33 acts not only as a positive regulator of salt tolerance (Jiang & Deyholos, 2009), thermo tolerance (Li et al, 2011), and systemic acquired resistance (Y. Wang et al, 2018), but as a negative regulator of SA accumulation and signalling as well (Birkenbihl et al, 2012; Zhang et al, 2019). Our results suggest that WRKY33 and ATL31 act synergistically by tightly controlling IRT1 homoeostasis in response to Cd stress and by regulating plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that WRKY33 exhibited a similar expression pattern to ATL31 and the expression levels of both genes were enhanced by Cd stress (Figures 1c,d, and 5g,h). Several studies have shown that WRKY33 acts not only as a positive regulator of salt tolerance (Jiang & Deyholos, 2009), thermo tolerance (Li et al, 2011), and systemic acquired resistance (Y. Wang et al, 2018), but as a negative regulator of SA accumulation and signalling as well (Birkenbihl et al, 2012; Zhang et al, 2019). Our results suggest that WRKY33 and ATL31 act synergistically by tightly controlling IRT1 homoeostasis in response to Cd stress and by regulating plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all abiotic stresses lead to the regulation of secondary oxidative stress stimulatory signals in a tissue-specific or even cell-specific manner ( Chaves and Oliveira, 2004 ). Increases in the corresponding enzyme activities under stress conditions protects plant cells from oxidative damage ( Chen et al, 2017 ; Zhang L. et al, 2020 ). To protect enzyme systems and membranes from lipid peroxidation, SOD, POD, and MDA activities increased at each growth stage after drought stress ( Gill and Tuteja, 2010 ; Abid et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, sharp upregulation in glyceraldehyde-3-phosphate dehydrogenase involved in the transfer of glyceraldehyde-3-phosphate to 1, 3-bisphosphoglycerate, was only abundant above the CN in embryos of aged ST seeds (Table 1). Cytoplasmic glyceraldehyde-3-phosphate dehydrogenase can be induced under many stress conditions, such as anoxia and salt toxicity, and is involved in seed aging (Zhang et al, 2020). Cytoplasmic glucose-6-phosphate isomerase was also upregulated significantly only above the CN in embryos of aged ST seeds (Table 1).…”
Section: Maintaining the Carbon Homeostasis Might Be Essential For Longer Plateau Phase During Aamentioning
confidence: 99%